Implementasi Sertifikat Halal Gratis Bagi Usaha Mikro Kecil Kota Depok - Gemilang Syauki Satriani; Izzatusholekha Izzatusholekha (Eksekusi : Jurnal Ilmu Hukum dan Administrasi Negara, 2024)
This study aims to determine the implementation of the free halal certificate policy in Depok city through Van Meter and Van Horn policy theory. The method used is descriptive qualitative. Data collection techniques are observation, interviews, and documentation. The results of the study are: The size and objectives of the policy adjust regulations and have guidelines for implementation and technical guidelines that regulate, and the implementation still has contradictions with the objectives and is too ideal in its implementation for MSE actors for success in October 2024. Long time resources in obtaining certification because MSE actors are less sensitive to technology. The characteristics of the implementing agent there are changes from the MUI Fatwa Commission to the Halal Product Fatwa Committee Task Team in determining halal products and changing regulations in the process of halal assistance to MSE actors which results in the need to be re-socialized and the Sihalal website which is sometimes slow in processing registration. The attitude and tendency of the implementers to have seriousness and commitment. Communication between organizations goes well between implementers will but socialization to MSE actors is still poorly implemented. Social, economic and political conditions have supported the policy, but the social conditions of MSEs are unstable and changing so that the target becomes difficult.